2020
DOI: 10.1002/bit.27552
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid inhibits Pseudomonas aeruginosa biofilm formation by activating diffusible signal factor‐mediated quorum sensing

Abstract: Bacterial biofilm formation causes serious problems in various fields of medical, clinical, and industrial settings. Antibiotics and biocide treatments are typical methods used to remove bacterial biofilms, but biofilms are difficult to remove effectively from surfaces due to their increased resistance. An alternative approach to treatment with antimicrobial agents is using biofilm inhibitors that regulate biofilm development without inhibiting bacterial growth. In the present study, we found that linoleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Even in bacteria such as Escherichia coli and Salmonella that do not produce AHLs (gram negative QS signalling molecule), it still possesses AHL response regulator protein, enabling it to respond to AHLs made by other bacteria. A third QS signalling molecule: Autoinducer-2 (AI-2), has been proposed as the signalling molecule used on an intra-species and inter-species level; facilitating communications between gram positive and negative bacteria [37][38][39]. It is important to note that although QS is essential for the formation of biofilms, the loss of this cell to cell communication system does not cause a lethal effect on bacterial cells [20].…”
Section: Quorum Quenchingmentioning
confidence: 99%
“…Even in bacteria such as Escherichia coli and Salmonella that do not produce AHLs (gram negative QS signalling molecule), it still possesses AHL response regulator protein, enabling it to respond to AHLs made by other bacteria. A third QS signalling molecule: Autoinducer-2 (AI-2), has been proposed as the signalling molecule used on an intra-species and inter-species level; facilitating communications between gram positive and negative bacteria [37][38][39]. It is important to note that although QS is essential for the formation of biofilms, the loss of this cell to cell communication system does not cause a lethal effect on bacterial cells [20].…”
Section: Quorum Quenchingmentioning
confidence: 99%
“…It was reported that palmitic acid had in vitro and in vivo efficacy against some bacteria, including Klebsiella pneumoniae , Escherichia coli and so on [ 52 ]. Kim et al [ 53 ] and Kim et al [ 54 ] found that linoleic acid had an inhibitory effect against pathogens such as Staphylococcus aureus , Candida albicans and Pseudomonas aeruginosa , etc. The above results of in vitro antibacterial activity assays ( Table 4 ) and in vivo antibacterial activity assays ( Figure 4 and Figure 5 ) prove that POEO had effective inhibitory activity against Pcc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DSF can block protease secretion from attack-phase cells of Bdellovibrio bacteriovorus 109 J completely at the concentration of 50 mM and negatively regulate the membrane integrity at a concentration of 200 mM [75]. Additionally, DSF inhibits biofilm formation with no impacts on the growth of P. aeruginosa under static and continuous conditions [76]. DSF also regulates intercellular public goods (such as extracellular polymeric substances (EPS) and amino acids) [76].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DSF inhibits biofilm formation with no impacts on the growth of P. aeruginosa under static and continuous conditions [76]. DSF also regulates intercellular public goods (such as extracellular polymeric substances (EPS) and amino acids) [76]. DSF-based QS systems are classified into three major classes, the first from Xcc, the second from Burkholderia cenocepacia and Cronobacter turicensis, and the third from Pseudomonas aeruginosa [77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%